REKONSTRUKSI KONSEP IJBAR - Hidayat, Taufiq (DE JURE, 2012)
Marriage is one of the pressing issues mentioned in detail in the Quran and hadis.  Sources  concerning  marriage  mirror  negotiation  between  patriarchal authority and equality among believers. Universal nature of the Quran is then interpreted and  implemented (tafsir wa-tatbiq) to fit the social and cultural makeup of pre-modern Arab peninsula. Hadis concerning forced marriage was put into the mouth of the  prophet to justify the patriarchal authority of pre- modern society, which finds its expression in the books of fiqh. It is a pity that, despite emancipation of women, tradition demeaning to women dies hard. This paper aims to analyze the concept of forced marriage discussed in the books of medieval fiqh which is considered outdated due to its violation of women’s right to choose their spouse.